Foreign Exchange Reserve Management And Economic Stability : A Case Study of Indonesia in Facing the Global Economic Slowdown - Nisa Septiani; Iwan Setiawan; Riani Winarni (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze the role and management strategies of foreign exchange reserves in maintaining Indonesia’s economic stability amid the global economic slowdown. The global slowdown, driven by geopolitical uncertainty, monetary policy tightening, and financial market volatility, has exerted pressure on developing countries, including Indonesia, through trade, exchange rate, and capital flow channels. This study employs a qualitative approach with a case study method, utilizing secondary data from reports of the International Monetary Fund (IMF), World Bank, and publications from Bank Indonesia. Data analysis is conducted using content analysis. The results show that the global economic slowdown has led to declining export performance, exchange rate volatility, and fluctuations in capital flows in Indonesia. In this context, foreign exchange reserves play a strategic role as a shock absorber in mitigating external pressures. However, their effectiveness is determined not only by the level of reserves but also by adaptive and prudent management strategies. This study highlights that economic stability is also influenced by the synergy between monetary and fiscal policies, as well as the strengthening of the domestic economic structure.